Impact of FDI on Performance of Select Private Sector Banks in India - Malla Reddy, M. (Indian Journal of Finance, 2016)
Foreign direct investment (FDI) is considered to be the lifeblood of economic development, especially for a developing country like India. It plays an important role in the long-run development of a country not only as a source of capital, but also for enhancing competitiveness of the domestic economy through transfer of technology, strengthening infrastructure, raising productivity, and generating employment opportunities. The financial sector is always the key sector for the overall development of any country, and the banking sector is the primary sector amongst all. Indian banking has come a long way since India adopted economic reforms in 1991. Today, Indian banks are as technology savvy as their counterparts in the developed countries. The competitive and reform forces have led to the emergence of the Internet, e-banking, ATM, credit cards, and mobile banking too in order to attract and retain the customers by a bank. This paper aimed at examining the impact of foreign direct investment on performance of select private sector banks such as Kotak Mahindra Bank Limited and IndusInd Bank Limited. Multiple linear regression technique was adopted to study the impact. This paper found that FDI had a significant positive impact on total business, business per employee (BPE), and total income of the banks; however, FDI had a negative impact on profit per employee (PPE) and total net profits of the selected banks.